2013
DOI: 10.1007/978-3-642-34952-2_1
|View full text |Cite
|
Sign up to set email alerts
|

The Web of Things - Challenges and Enabling Technologies

Abstract: Advances in ubiquitous computing and embedded systems are closing the gap between the physical and virtual worlds. With the Internet becoming the platform of choice for communication, ubiquitous computing faces new opportunities and challenges. Today, things like refrigerators and bathroom scales are becoming Internet enabled and the trend is increasing with Internet penetration predicted to cover a wide range of physical appliances. The Internet of Things (IoT) is an active research area, focusing on connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…We define Ambient Spaces (AS) to be the virtual representations of one or more Web-enabled things that is within such specific spatial contexts, and has information or operations to be represented on the Web [9]. The use of AS has made it possible to represent a large number of physical things and thereby enabling real-world things and people to seamlessly communicate [10,11]. Novel applications are envisioned in these spaces within the scope of WoT extending accessibility to everyone and for everything from a Web browser.…”
Section: Introductionmentioning
confidence: 99%
“…We define Ambient Spaces (AS) to be the virtual representations of one or more Web-enabled things that is within such specific spatial contexts, and has information or operations to be represented on the Web [9]. The use of AS has made it possible to represent a large number of physical things and thereby enabling real-world things and people to seamlessly communicate [10,11]. Novel applications are envisioned in these spaces within the scope of WoT extending accessibility to everyone and for everything from a Web browser.…”
Section: Introductionmentioning
confidence: 99%
“…Atzori et al [9] suggested a new concept called the Social Internet of Things, in which social networks of things are composed within the Internet of Things. In addition, other studies have attempted to connect devices together in terms of their social relations [10]- [17].…”
mentioning
confidence: 99%
“…Díaz-Sánchez et al [8] developed a social enabler and watchdog through which a home gateway conducts requests to social networks on behalf of the home devices, thereby connecting the home devices to a social network service. Similar to a human on-line social network service connecting users together through the Internet and Web technologies, devices can be easily connected based on their social relation with other devices [9]- [17]. Atzori et al [9] suggested a new concept called the Social Internet of Things, in which social networks of things are composed within the Internet of Things.…”
mentioning
confidence: 99%
“…they are participating members of the Web), they are grouped/clustered into an Ambient Spaces (AS) [10,9]. An AS is the virtual representation of a cluster of things i.e.…”
Section: Representation Of Things On Wotmentioning
confidence: 99%
“…In our architecture, we use a customized version of the well-known ISO reference monitor standard [9].…”
Section: Policy Enforcement Facitiliesmentioning
confidence: 99%